GREEN SUPPLY CHAIN MANAGEMENT AND CUSTOMER SATISFACTION: A STRATEGIC IMPERATIVE FOR SUSTAINABLE BUSINESS - Navneet Kumar; Dokhoria, Shivani (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Green Supply Chain Management (GSCM) has emerged as a key driver of customer satisfaction in today's sustainability-focused business environment. As consumers increasingly prioritize eco-friendly products and ethical business practices, companies integrating GSCM strategies gain a competitive advantage. This paper examines how sustainable sourcing, eco-friendly packaging, and carbon footprint reduction influence customer perceptions and behaviors. Additionally, it explores the challenges businesses face, such as balancing sustainability with operational efficiency and overcoming greenwashing skepticism. The role of technology, including AI and blockchain, in enhancing transparency and verifying sustainability claims is also discussed. Finally, the paper highlights gaps in existing research and suggests future directions for a more consumer-driven and sustainable supply chain.